Rhetorical Moves in Research Article Introductions of Students of Linguistics Master Program (e-Journal of Linguistics, 2020)
This research investigated the rhetorical moves in theintroduction part to the research article written by graduatestudents in Linguistics master's study programs. The primarypurpose of this research is to describe the pattern of rhetoricalmoves in the research article introductions in the field ofLinguistics. The data collection technique was in the form ofscientific article documentation consisting of seven researcharticle introductions in English in the field of Linguistics.Researchers collected data in the form of text with documentanalysis and note-taking techniques. These research articles weretaken from four different journal publishers in Indonesia, namelyAlphabet, Kelasa, Batra, and Suar Betang. The rhetoricalanalysis in this study involves the concept of the ProjectJustifying Model (PJM) proposed by Safnil (2010), whichconsists of four communicative moves that can describe therhetorical moves of Indonesian writers. The validity of the datain this rhetorical pattern study used the triangulation of sourcesor data. The results of this study indicate that the sevenintroductions have different rhetorical moves. The four researcharticle introductions taken from the Alphabet produced fewerrhetorical steps compared to the other three research articles. Themost dominant signal found in the seven research articleintroductions is (move 4, step A) represents a statement inexplaining the purpose of the study. The seven research articleintroductions found no statements that represented the five stepscontained in each move.
Keywords: rhetorical moves; research article introductions; graduate students